Antecedents of Visiting Decisions on Artificial Travel Destinations: Millennial Generation Perspectives - Sukaris, Sukaris (INNOVATION RESEARCH JOURNAL, 2020)
The purpose of this study was to determine the effect of tourist motivation, electronic word of mouth and destination image on the decision to visit the Gunung Mas Palace in Lamongan. The sample uses non probability sampling method with a purposive sampling or random sampling procedure by selecting 106 visitors. The data analysis technique uses multiple linear regression. The results of multiple linear regression analysis prove that tourist motivation and destination image proved not to have a significant effect partially on decisions leading to Gunung Mas Palace in Lamongan, while electronic word of mouth proved to have a partially significant influence on the decision to visit the Gunung Mas Palace in Lamongan